International Conference Wood Science and Engineering in the Third Millennium - ICWSE 2023 (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
The global demand for wood is steadily increasing, driven by various factors such as population growth, urbanization, and a shift towards sustainable and renewable materials. As industries and consumers alike seek eco-friendly alternatives, wood's versatility and environmental benefits make it a preferred choice. This reprint focuses on research related to innovative solutions to optimize wood utilization and contains studies spanning several subject areas, including explorations of subfossil, lesser-known and fast-growing species, and advanced composites. Meeting future material requirements while addressing potential wood shortages involves efficient resource management and advancements in wood processing, preservation, and technological applications. This reprint demonstrates that these efforts enable the production of high-added-value products and sustainable development within the wood industry.